SEMANTIC SIMILARITIES AND DIFFERENCES IN THE VOCABULARY OF THE ENGLISH, UZBEK AND RUSSIAN LANGUAGES - Tashlanova Nigora Djuraevna (Modern American Journals, 2025)
This article reveals semantic similarities and differences in the vocabulary of the color designation of English, Uzbek and Russian languages, about the linguistic picture of the world, which gives all kinds of ideas about the national mentality of different languages, since universal knowledge and achievements with a greater or lesser degree of adequacy can be transmitted through linguistic means.
Keywords: Semantic similarities, vocabulary of color designation, linguistic picture of the world, comparative study, body of knowledge about the world, linguistics, interpretation, universal knowledge.